ADAPTATION OF TELECOMMUNICATION TECHNOLOGY BY ICT COMPANIES - Ab Yajid, Mohd Shukri; Johar; MGM; Azam, S.M. Ferdous (International Journal of Psychosocial Rehabilitation, 2020)
Cost of telecommunication companies have become one of the top expense in most of the companies because of the offering of services and complexities via rapid growth. There is need of understanding of the complex and erotic ways of services, features and technologies. The study conducted will attempt to identify and measure the adaptation of telecommunication technology, particularly VoIP service by ICT companies in Malaysia. A set of extensive questionnaire is developed in order to provide this study with qualitative and quantitative results. The sample used for this study comprise 80 working class of employees from ICT companies were targeted at the main cities in Malaysia. The findings from this study signify that the impact caused from the evolution of telecommunication technology especially the emergence of VoIP service apparently have indicated positive response towards the adaptation of new telecommunication technology by ICT companies in Malaysia.